2016
DOI: 10.1186/s11671-016-1532-4
|View full text |Cite
|
Sign up to set email alerts
|

Micro/Nano Multilayered Scaffolds of PLGA and Collagen by Alternately Electrospinning for Bone Tissue Engineering

Abstract: The dual extrusion electrospinning technique was used to fabricate multilayered 3D scaffolds by stacking microfibrous meshes of poly(lactic acid-co-glycolic acid) (PLGA) in alternate fashion to micro/nano mixed fibrous meshes of PLGA and collagen. To fabricate the multilayered scaffold, 35 wt% solution of PLGA in THF-DMF binary solvent (3:1) and 5 wt% solution of collagen in hexafluoroisopropanol (HFIP) with and without hydroxyapatite nanorods (nHA) were used. The dual and individual electrospinning of PLGA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 74 publications
1
38
0
2
Order By: Relevance
“…Composites made of collagen and hydroxyapatite (HA) are attractive biocompatible materials as they possess the organic and mineral constituents of bone [46][47][48]. Scaffolds made of collagen and HA with/without synthetic polymers have been widely produced by electrospinning (ES) [49][50][51][52] and conventional scaffold fabrication techniques [53][54][55][56][57]. The flexibility of generating broad pore size ranges and mechanical properties by additive manufacturing (AM) makes it a superior alternative to ES and conventional techniques [58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…Composites made of collagen and hydroxyapatite (HA) are attractive biocompatible materials as they possess the organic and mineral constituents of bone [46][47][48]. Scaffolds made of collagen and HA with/without synthetic polymers have been widely produced by electrospinning (ES) [49][50][51][52] and conventional scaffold fabrication techniques [53][54][55][56][57]. The flexibility of generating broad pore size ranges and mechanical properties by additive manufacturing (AM) makes it a superior alternative to ES and conventional techniques [58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…Demonstrating that the homogeneous dispersion of glutamic acid-modified hydroxyapatite nanoparticles (nHA-GA) in the COL solution improved the osteogenic properties of the multilayer scaffolds fabricated. In addition, it found that PLGA-COL-HA micro-nano fibrous scaffolds were highly bioactive compared to pristine microfibrous PLGA and PLGA and COL micro/nano-mixed fibrous platforms [26].…”
Section: Collagen Electrospinningmentioning
confidence: 97%
“…Designing the hierarchical micro/nanoscaled scaffolds for tissue generation could (1) modulate the functional response of cell; (2) induce structural and functional integration of cells and tissues; (3) control the process of tissue remodeling by the structure and component modulation of hierarchical network. Recently, considerable research efforts have been made to develop various hierarchical micro/nanostructured scaffolds for bone repair, Achilles tendons, rotator cuffs, and skin tissue . Dura mater is a connective tissue membrane composed mainly of hierarchical collagen fibers with various diameters, multilayers, and orientations .…”
Section: Introductionmentioning
confidence: 99%